Cumulative Summation (CUSUM)—as a tool for objective analysis of learning curve for surgeons in acquiring competency in phacoemulsification - Emily Ming Choo Ng; Mohamad Aziz Salowi; Othmaliza Othman; Rosmawati Uthman; Nor Fariza Ngah (BMC Ophthalmology)
Abstract Background Phacoemulsification is the most widely performed cataract surgery and a key indicator of surgical competency for ophthalmologists. This study applies cumulative summation (CUSUM) analysis to a large national dataset to identify the number of cases required for trainees to reach proficiency, with the goal of enhancing training standards and ensuring patient safety. Methods This retrospective study focuses on the phacoemulsification performed at the healthcare centres under the Ministry of Health, Malaysia. The study used data from the web-based Cataract Surgery Registry. The target group consisted of provisional surgeons who completed the training programme between January 1, 2013, and December 31, 2020. As posterior capsular rupture (PCR) is the most common complication in phacoemulsification, it is widely accepted as a competency benchmark. The study utilised CUSUM analysis to assess the occurrence of PCR for consecutive cases. The average CUSUM scores of all surgeons were plotted to generate a graph. The point at which the learning curve levels off was determined by employing a polynomial graph in Microsoft Excel. Results Our result was based on the phacoemulsification cases performed by a cohort of 230 provisional surgeons. By aggregating the CUSUM scores of all participating surgeons, we observed that the graph representing the learning curve reached a plateau after 75 cases. Conclusion The learning curve was constructed using the CUSUM score, and surgeons required at least 75 cases to achieve competency in phacoemulsification.